Operational risk management in banks and idiosyncratic loss theory : a leadership perspective - Velez, Sophia Beckett (Emerald Publishing Limited, 2022)
A systemic risk event that leads to significant losses in banks that are significant financial institutions can expose them to insolvency, significant volatility and impose serious negative impact on a country's economy, as witnessed during the 2008 financial crash. The viral spread of operational losses through global markets by interconnected multinational banks can be referred to as idiosyncratic viral loss theory. Operational Risk Management in Banks and Idiosyncratic Loss Theory: A Leadership Perspective identifies important considerations that can bolster effective risk management practices in comprehensive enterprise-wide risk, fraud control, going beyond minimum risk assessment required by banking regulators as well as independent risk identification and management. These considerations towards improving risk management practices may help reduce systemic operational losses spread virally in banks. Operational Risk Management in Banks and Idiosyncratic Loss Theory is a useful tool for scholars, bank practitioners, regulators, and accountants to understand the behaviour of idiosyncratic viral losses in banks and in the use of effective risk management practices. Bank practitioners and regulators can leverage the suggestions made by the panel of sector experts and bank leaders to construct action plans and training programs.